Strategic Behaviours in a Labour Market with Mobility-Restricting Contractual Provisions: Evidence from the National Hockey League - Luca Fumarco; Neil Longley; Alberto Palermo; Giambattista Rossi (Institute of Labor Economics (IZA), 2024)
We follow workers' performance along an unbalanced panel dataset over multiple years and study how performance varies at the end of fixed-term contracts, in a labour market where some people face a mobility restricting clause (i.e., a noncompete clause). Focusing on the labour market of the National Hockey League, we analyse players' performance data and contracts with a fixed effect estimator to address empirical limitations in previous studies. We find that, on average, NHL players' performance does not vary. However, our estimations detect substantially heterogeneous behaviours, depending on tenure, perceived expected performance and mobility. Only younger players (i.e., restricted free-agents) with high expected mobility but low expected performance tend to behave strategically and perform better. Differently, older players (i.e., unrestricted free-agents) with high expected mobility tend to underperform, as the option of moving back to European tournaments is more appealing.
Keywords: D82; J24; J33; M52; Z22; 330; strategic behaviour; mobility; noncompete clauses